TRANSFORMATIONAL LEADERSHIP, WORK MOTIVATION ON JOB SATISFACTION, EMPLOYEE PERFORMANCE AT NATIONAL AMIL ZAKAT INSTITUTION - Muklis Muklis; Riyadi Nugroho; Slamet Riyadi (International Journal Labs, 2022)
Purpose. The purpose of this study is to prove and analyze the performance of employees at the head office of the Yatim Mandiri National Amil Zakat Institution in Surabaya. This study uses four variables, namely transformational leadership, work motivation, job satisfaction, and employee performance. Design. With a population of 170 and a sample of 140, respondents were calculated using the Slovin formula. The sampling method is an intentional sampling from the sampling group with low probability. This study uses a survey method to collect quantitative data by using a questionnaire data analysis used by SEM in the Amos 26 program. Findings. According to this study, it shows that: 1) transformational leadership affects employee job satisfaction. 2) Transformational leadership affects employee performance. 3) Work motivation is very influential on employee job satisfaction. 4) Work motivation affects employee performance. 5) Job satisfaction affects employee performance. To find out that transformational leadership has the strongest influence on employee performance. Implications. The results of this study imply that when leaders carry out management well, the indicators of work motivation variables may have a strong effect on increasing employee job satisfaction. In addition, in a good management process by dividing the indicators of transformational leadership variables and indicators of work motivation variables that are adjusted to the characteristics of employees also has a strong effect on improving employee performance. In addition, the indicator of job satisfaction variable carried out in carrying out good management also has a strong effect on improving employee performance. Recommendation. The following researchers are encouraged to conduct research on the effect of transformational leadership, work motivation, job satisfaction, and employee productivity.